2007
DOI: 10.1097/01.ncc.0000265013.63547.4a
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Cancer Patients With Palliative Care Needs

Abstract: The aim of this study was to examine UK district nurses' perceptions of their role in supporting palliative care cancer patients. Patients with cancer are living longer with the disease. District nurses are the largest UK workforce caring for people with cancer at home, the preferred place of care. Meeting patients' supportive and palliative care needs is complex. Little is known about district nurses' supportive role in the early phase of palliative care. Semistructured interviews were conducted with 34 distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…This was confirmed by research [21], which found that it is crucial to come in at an early stage to establish a good relationship. Establishing a relationship with the patient and relatives early creates the conditions for person-centred care in palliative care.…”
Section: Discussionmentioning
confidence: 64%
“…This was confirmed by research [21], which found that it is crucial to come in at an early stage to establish a good relationship. Establishing a relationship with the patient and relatives early creates the conditions for person-centred care in palliative care.…”
Section: Discussionmentioning
confidence: 64%
“…Other evidence suggests however that DNs lack confidence in communication skills and in assessing cancer patients' psycho-social needs; also that they lack time for this work (Dunne et al, 2005;Aitken, 2006;Addington-Hall et al, 2006;Griffiths et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that early contact with the patient is essential and that homecare nurses sometimes contact the patient already in the hospital. Griffiths et al (2007) also showed the importance of an early contact. Yet, Pateman, Wilson, McHugh and Luker (2003) found that patients could experience this early contact as negative.…”
Section: Discussionmentioning
confidence: 91%
“…Community nursing has shown to offer stimulation and appreciation, especially from patients and relatives, but also a possibility for nurses to use all their professional skills (Dunne et al, 2005;Goodman et al, 1998). However caring for palliative cancer patients in their homes has also been shown to be stressful (Bertero, 2002;Dunne et al, 2005), emotionally burdensome (Griffiths et al, 2007) and causing feelings of powerlessness (de Schepper, Francke & Abu-Saad, 1997). The knowledge of community nurses' role has increased during the last years, but there is a paucity of knowledge on community nurses in palliative home nursing care.…”
Section: Introductionmentioning
confidence: 99%